THE ESTABLISHMENT OF UKRAINIAN-POLISH DIPLOMATIC RELATIONS - Voskoboinyk, K. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
The article analyzes the formation of diplomatic relations between Ukraine and the Republic of Poland, which became possible due to radical changes in Europe at the end of the XX century. The collapse of the Soviet Union, the emergence of independent Ukraine, the collapse of the communist system in Poland, the geopolitical location of countries, territorial proximity, traditional economic ties and mutual interest have created favorable conditions for the establishment and rapid development of bilateral relations between Ukraine and the Republic of Poland. Dialogue between the Ukrainian and Polish elites, begun under the conditions of radical changes that were gaining momentum in the USSR, have positively affected the development of external relations between the above-mentioned states. The article focuses on the formation of a contractual and legal basis for bilateral cooperation between Ukraine and the Republic of Poland. The establishment of which was at the initial stage of the formation of Ukraine as an independent state in the territory of Europe. The conceptual foundations of Ukrainian-Polish relations are highlighted.